Near-Complete Hand Loss Following an Unintentional, Intra-arterial Medicine Injection in an Infant - Bulic, Kresimir; Antabak, Anko; Lorencin, Mia (Journal of Pediatric Intensive Care, 2018)
Unintentional, intra-arterial administration of medicines can lead to very serious sequelae, including limb loss. We present a case of a 13-week-old boy who was unintentionally given phenobarbital into his right radial artery, which resulted in a near-complete hand amputation. Pediatric patients are under increased risk of such injuries due to their small vessel size and their inability to express immediate complaints, which often leads to a delayed recognition of the condition. As no specific treatment algorithms have been established, the mainstay of therapy is supportive care aimed at maintaining vascular patency. Prompt recognition is imperative in avoiding potentially detrimental effects; therefore, all personnel administering intravenous therapy should be aware of this possibility and be acquainted with the initial supportive measures.
Keywords: intra-arterial injection; hand amputation; phenobarbital; infant